Analysis of pre-service TESL teachers technological pedagogical content knowledge for teaching of English language as a second language - Mohd Zulkharnain Mohd Kasim (2021)
The study investigates pre-service teachers perceptions of TPACK in teaching English Language and identifies the challenges faced by the pre-service teachers during their practicum in term of teaching and learning. A qualitative research approach was used in this study. The methods for gathering data were classroom observations, semistructured interviews, and document analysis. Four English as a Second Language (ESL) pre-service teachers were selected using the purposive sampling method. Four pre-service teachers who were in their final year did their practicum in two different schools in Shah Alam. Each teacher was observed five times over a period of twenty lessons. Non-participant observation was conducted during the teaching sessions. A checklist was used during the observation to ensure uniformity in the elements observed during each lesson. The findings of this study revealed that the pre-service teachers were all equipped with the three knowledge domains in TPACK namely Technological Knowledge, Pedagogical Knowledge and also the Content knowledge. Another significant finding was that the opportunities given were different from each school, therefore the chances of applying their knowledge on the three domains relied on the facilities and opportunities provided by the schools. In conclusion, the study showed that the pre-service teachers have a substantial understanding and mastery of TPACK. The pre-service teachers revealed some effective technological pedagogical content knowledge strategies used for teaching purposes to capture students interest to make learning more fun and meaningful. The implication of this study is that the pre-service teachers will have an overview about the challenges and whether or not it is necessary for them to acquire TPACK on the quest of being a good teacher.